Bone mineral density determinants in adolescents and young adults with congenital adrenal hyperplasia - Navardauskaite, Ruta; Vanckaviciene, Aurika; Verkauskiene, Rasa (Frontiers in Pediatrics, 2024)
The effects of long-term glucocorticoid (GC) treatment on bone mineral density (BMD) in patients with congenital adrenal hyperplasia (CAH) remain controversial.Objectives: This cross-sectional study aimed to evaluate BMD in relation to genotype, growth, vitamin D status, cumulative GC doses, and other relevant factors in youth with CAH.Methods: Thirty-two patients with classical CAH (13 males; mean age 26.0 ± 7.1 years) were compared with 32 healthy controls matched by age and sex. BMD was measured using dual-energy Xray absorptiometry (DXA), and statistical analyses, including the Mann-Whitney U test and Spearman's correlation coefficient, were performed to evaluate differences and associations.Results: Median whole-body and lumbar BMD Z-scores were similar between CAH patients and controls (p = 0.27, p = 0.15, respectively). Low bone density was observed in 12.5% of CAH patients and 18.75% of controls (p = 0.5), while osteoporosis was confirmed in 12.5% of CAH patients and 0% Navardauskaite R., et al.of controls (p = 0.04). BMD did not correlate with cumulative GC doses, estradiol, renin, phosphate, sodium levels, or anthropometric parameters in CAH patients. There was no significant difference in BMD between severe and non-severe genotypes of CAH. However, a positive correlation was found between whole-body BMD Z-score and growth velocity during infancy (r = 0.776, p = 0.021) in CAH patients. Vitamin D deficiency was noted in 56.25% of CAH patients, although vitamin D levels did not correlate with BMD or genotype. No history of bone fractures was reported among study participants.Conclusions: Patients with CAH are at risk of developing osteoporosis, but in this study, BMD Zscores were not associated with cumulative GC doses. The study did not identify an association between genotype and BMD. Poor growth during infancy was linked to decreased BMD in adulthood.